Wartości społeczne i kulturowe obecne w "Przeglądzie Sportowym" w latach 1935-1945 = The social and cultural values present in the "Sport Review" in the years 1935-1945 - Ast, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It is commonly known that sport, or physical culture in general, is the source and reflection of human ideals and values that are worth striving foroku. This article constitutes one of many pieces of evidence that sport is a rich source of values and anti-values.
Keywords: literatura; sport; wartości; poezja sportowa; kultura fizyczna; czasopiśmiennictwo; społeczeństwo; literature; values; sports poetry; phisical culture; periodicals; society